Ad Hoc Wireless Routing Schemes based on Adaptive Modulation in OFDM Broadband Networks - Wee, Sian Wong; Chong, Eng Tan (IEEE, 2008)
In order to facilitate communication within an ad hoc wireless network, a routing protocol is required to route data between nodes. The primary goal of such routing protocol is correct and efficient information exchange between the nodes. This paper addresses such routing issue from the Physical Layer perspective of an Orthogonal Frequency Division Multiplexing (OFDM) broadband ad hoc wireless network. Two wireless routing schemes, namely, the Adaptive-All and Adaptive-Select Routing Scheme were proposed, based on the Channel Impulse Response (CIR) of the wireless channel. Extensive simulation results show that both of the schemes are efficient in reducing the error rate and increasing the data throughput.